2017
DOI: 10.15761/tim.1000119
|View full text |Cite
|
Sign up to set email alerts
|

Fetal nasal bone hypoplasia in the second trimester and risk of abnormal karyotype in a population of Chinese pregnant women

Abstract: Introduction: To evaluate the association of hypoplastic nasal bone and fetal chromosomal abnormalities in a prescreened sample of Chinese pregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…So, the use of nasal bone length percentiles in screening may be impractical for different ethnic groups. Yan Du et al reported the hypoplastic nasal bone rate as 1.15% in the Chinese population by using 2.5% rates described in other studies [ 12 ]. As the evaluation of the fetal face may be difficult in the late second and third trimester, due to the position of the fetus, ultrasound assessment of nasal bone is more favorable in the early second trimester [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…So, the use of nasal bone length percentiles in screening may be impractical for different ethnic groups. Yan Du et al reported the hypoplastic nasal bone rate as 1.15% in the Chinese population by using 2.5% rates described in other studies [ 12 ]. As the evaluation of the fetal face may be difficult in the late second and third trimester, due to the position of the fetus, ultrasound assessment of nasal bone is more favorable in the early second trimester [ 13 ].…”
Section: Introductionmentioning
confidence: 99%